Health profile of people living in the Gare Palma mining area of Tamnar block, Raigarh, Chhattisgarh, India - Shrivastava, Suyesh; Kumar, Ravindra; Khan, Sirin; Kavishwar, Arvind; Gupta, Ashok; Kaur, Harpreet; Das, Madhuchanda; Sharma, Ravendra; Chakma, Tapas (Frontiers in Public Health, 2023)
The aim of the study was to evaluate the morbidity profile and associated risk factors for communicable and non-communicable diseases among adult residents of rural and industrial (mining) areas of Raigarh district. A community-based health survey was conducted in Tamnar block, Raigarh district of Chhattisgarh from March 2019 to February 2020. A total of 909 individuals (adults) were selected from 909 households from 33 sampled villages. All individuals were clinically examined and observations were recorded. Acute dermatitis and acute respiratory infections were common morbidities observed in studied participants. Hypertension and type II diabetes mellitus was observed in 21.7% and 4.0% individuals respectively. Pulmonary tuberculosis was seen in 23(2.5%) individuals. Common morbidities were observed in similar frequency in tribals and non-tribals living in the same area. For communicable disease; male gender, nutritional deficiency and smoking behaviour were independent risk factors. For non-communicable diseases; the independent significant risk identified were male gender, altered body mass index, disturbed sleep, smoking behaviour and nutritional deficiency.